A tempered corrosion-resistant colored coated glass and its preparation process

By thiolizing the silica prepolymer in the coating solution, and introducing modified silica sol and graphite-doped epoxy silane oligomers, forming a network interconnect structure, the problems of poor corrosion resistance, poor wear resistance and low hardness of coated glass are solved, and the effect of significantly improving wear resistance and hardness is achieved.

CN119371115BActive Publication Date: 2025-04-04WEIFANG HONGXING TOUGHENED GLASS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411930364.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing coated glass has poor corrosion resistance, poor wear resistance and low hardness, which limits its application range.

Method used

By thiolizing the silica prepolymer in the coating solution, and introducing modified silica sol and graphite-doped epoxy silane oligomers, a network interconnection structure is formed to improve the corrosion resistance, wear resistance and hardness of the coated glass.

Benefits of technology

It achieves good corrosion resistance of coated glass, significantly improves wear resistance and hardness, and expands its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of glass materials, and specifically relates to a tempered corrosion-resistant colored coated glass and a preparation process thereof. The present invention effectively ensures that the coated glass has good corrosion resistance and effectively improves its wear resistance by mercapto-modifying the silicon dioxide prepolymer in the coating solution and introducing modified silica sol and graphite-doped epoxy silane oligomer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass materials, and in particular relates to a tempered corrosion-resistant colored coated glass and a preparation process thereof. Background Art

[0002] Glass is closely related to the progress of human civilization and has become an indispensable material for human life. As early as the Middle Ages, glass was used in church decoration. In the 20th century, glass has become an important building material. Energy-saving glass and smart glass have been rapidly developed and widely used. Coated glass has excellent heat insulation and thermal insulation properties. In the current situation of energy shortage, energy conservation and green environmental protection in the world, it is one of the main building materials that are indispensable for building energy conservation. Coated glass is mainly achieved by depositing one or more layers of thin film materials (such as metal, alloy or metal compound thin film) on the surface of the glass substrate, thereby changing the optical, electrical and mechanical properties of the glass to meet the needs of different fields and multiple functions such as energy conservation, decoration and environmental protection.

[0003] A Chinese patent (publication number CN117142772B) provides a self-cleaning coated glass and its preparation method, using inorganic glass as a glass substrate, firstly etching to obtain a highly hydrophilic and easily modified glass substrate, then in-situ growing nano zinc oxide, nano silicon oxide and introduced bi-electric chitin nanofibers on the surface of the glass substrate by immersion and pulling to jointly construct an anti-reflection layer, and coating the anti-reflection layer with a self-cleaning protective coating to give the coated glass a self-cleaning, anti-fouling, antibacterial and self-repairing surface. However, the patent does not solve the problems of poor corrosion resistance, poor wear resistance and low hardness of coated glass in the prior art, which seriously affects its application scope.

[0004] Therefore, there is an urgent need for a tempered corrosion-resistant colored coated glass. By modifying the coating liquid components, the coated glass can have good corrosion resistance and effectively improve its wear resistance. Summary of the invention

[0005] The purpose of the present invention is to provide a tempered corrosion-resistant colored coated glass and a preparation process thereof, by mercapto-modifying the silicon dioxide prepolymer in the coating solution and introducing modified silica sol and graphite-doped epoxy silane polymer, the coated glass is effectively guaranteed to have good corrosion resistance and its wear resistance is effectively improved.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The first aspect of the present invention provides a process for preparing a tempered corrosion-resistant colored coated glass, comprising the following steps:

[0008] Step S1: in parts by weight, 40-50 parts of tetraethyl orthosilicate, 50-60 parts of isopropanol, 1-3 parts of glacial acetic acid and 12-16 parts of deionized water are mixed evenly, hydrolyzed at room temperature for 30-40 hours, then heated to 70-80° C. for reaction for 2-4 hours, cooled to room temperature, added with 2-4 parts of (3-mercaptopropyl) triethoxysilane, stirred and reacted for 20-24 hours, to obtain a mercapto-silica prepolymer;

[0009] Step S2: in parts by weight, 25-35 parts of mercapto-silica prepolymer, 15-25 parts of silane coupling agent, 16-18 parts of isopropanol, 20-30 parts of silica sol, 1-2 parts of surfactant and 4-8 parts of propylene glycol butyl ether are uniformly mixed, stirred at 48-50° C. for 2-4 hours, and after cooling to room temperature, 6-10 parts of epoxy silane oligomer and 180-200 parts of isopropanol are added and stirred for 40-60 minutes to obtain a coating solution;

[0010] Step S3: coating the coating liquid on the surface of the glass substrate, and then performing a curing treatment to obtain a tempered, corrosion-resistant colored coated glass.

[0011] By introducing mercapto groups, the mercapto-silica prepolymer can promote a more uniform distribution of the prepolymer on the glass surface, reduce defects and pores in the coating layer, and at the same time, the mercapto-silica particles can fill into the tiny pores on the glass surface, further improving the continuity and protective performance of the coating layer, increasing the corrosion resistance of the material, and reducing the haze of the coated glass.

[0012] As a preferred solution, the silica sol is a modified silica sol; the preparation method of the modified silica sol comprises: in parts by weight, 50-60 parts of anhydrous ethanol and 10-20 parts of deionized water are mixed evenly, then 40-50 parts of ethyl silicate 40 are added, stirred at 50-60°C for 2-4 hours, after cooling to room temperature, 2-4 parts of hydrochloric acid are added and stirred for 20-24 hours, and then 4-6 parts of calcium sulfate whiskers are added and stirred for 20-30 minutes to obtain a silica sol coated with calcium sulfate; 1-3 parts of 3-aminopropyltriethoxysilane are added to 60-80 parts of the silica sol coated with calcium sulfate, the pH is adjusted to 7.4-7.6, and the reaction is stirred at 60-70°C for 12-14 hours to obtain the modified silica sol.

[0013] As a preferred solution, the diameter of the calcium sulfate whisker is 3-5 μm.

[0014] Calcium sulfate whiskers have high strength and help disperse stress and prevent crack expansion, which can improve the glass's ability to resist scratches and wear. The nano-silica particles in the silica sol can fill tiny pores. Calcium sulfate whiskers provide mechanical reinforcement on a macro scale, while the silica sol fills gaps and enhances interface bonding at a micro level. The synergistic effect of the two can greatly improve the wear resistance of coated glass and increase the visible light transmittance after wear.

[0015] As a preferred solution, the epoxy silane polymer is a graphite-doped epoxy silane polymer; the preparation method of the graphite-doped epoxy silane polymer comprises: heating 30 to 40 parts of epoxy silane polymer to 50 to 60° C. by weight, then adding 2 to 4 parts of carboxylated graphite and stirring for 40 to 60 minutes, and then vacuum degassing at 60 to 70° C. for 30 to 40 minutes to obtain the graphite-doped epoxy silane polymer.

[0016] As a preferred scheme, the preparation method of the carboxylated graphite comprises: weighing 4 to 6 parts of graphite by weight and dispersing them in a mixed solution of 10 to 20 parts of sulfuric acid and 20 to 30 parts of nitric acid for ultrasonic dispersion treatment, then reacting them under hot reflux at 150 to 160° C. for 1 to 3 hours, washing the product with deionized water, and drying to obtain acidified graphite; dispersing 4 to 6 parts of the acidified graphite in 100 to 120 parts of N,N-dimethylformamide to obtain a suspension, adding 6 to 8 parts of N,N'-dicyclohexylcarbodiimide, 1 to 3 parts of 4-dimethylaminopyridine and 8 to 10 parts of acrylic acid to the suspension, reacting them at 80 to 90° C. for 20 to 24 hours under the protection of a nitrogen atmosphere, filtering, washing, and drying to obtain the carboxylated graphite.

[0017] As a preferred solution, the particle size of the graphite is 2-5 μm.

[0018] The graphite in the graphite-doped epoxy silane polymer has high hardness and wear resistance. At the same time, it is modified by carboxylation to ensure that it can be evenly dispersed in the epoxy silane polymer. The siloxane part in the epoxy silane polymer can chemically bond with the glass surface to create a strong interface layer and ensure that the graphite particles are firmly attached to the glass surface. The combined effect significantly improves the hardness of the coated glass.

[0019] As a preferred solution, the silane coupling agent is selected from any one of methyltrimethoxysilane, 3-aminopropyltriethoxysilane, and γ-glycidyloxypropyltrimethoxysilane, or a combination of at least two thereof.

[0020] As a preferred solution, the surfactant is selected from any one of cetyltrimethylammonium bromide, dodecyldimethylbenzylammonium chloride, didodecyldimethylammonium chloride, or a combination of at least two thereof.

[0021] As a preferred solution, the curing temperature of the curing treatment is 80-160° C., and the curing time is 6-10 min.

[0022] The second aspect of the present invention provides a tempered, corrosion-resistant colored coated glass prepared by the process described in the first aspect.

[0023] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0024] 1. The graphite-doped epoxy silane oligomer of the present invention contains active groups of epoxy and carboxyl. On the one hand, the epoxy can react with the mercapto-silica prepolymer, and the mercapto as a nucleophilic agent attacks a carbon atom in the epoxy to form a new chemical bond; on the other hand, the carboxyl can combine with the amino group of the modified silica sol to form an amide bond, thereby forming a network interconnected structure, which effectively improves the wear resistance and hardness of the coated glass while achieving corrosion resistance.

[0025] 2. The mercapto-silica prepolymer of the present invention can promote a more uniform distribution of the prepolymer on the glass surface by introducing mercapto groups, thereby reducing defects and pores in the coating layer. At the same time, the mercapto-silica particles can be filled into the tiny pores on the glass surface, further improving the continuity and protective performance of the coating layer, increasing the corrosion resistance of the material, and reducing the haze of the coated glass.

[0026] 3. The calcium sulfate whiskers of the present invention have high strength and help to disperse stress and prevent the expansion of cracks, thereby improving the ability of glass to resist scratches and wear. The nano-silicon dioxide particles in the silica sol can fill tiny pores. The calcium sulfate whiskers provide mechanical reinforcement on a macro scale, while the silica sol fills the gaps and enhances interface bonding at a micro level. The synergistic effect of the two can greatly improve the wear resistance of the coated glass and increase the visible light transmittance after wear.

[0027] 4. The graphite in the graphite-doped epoxy silane polymer of the present invention has high hardness and wear resistance. At the same time, it is guaranteed to be evenly dispersed in the epoxy silane polymer after carboxyl modification. The siloxane part in the epoxy silane polymer can chemically bond with the glass surface to create a strong interface layer and ensure that the graphite particles are firmly attached to the glass surface. The combined effect significantly improves the hardness of the coated glass. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The sources of some components in the embodiments and comparative examples are as follows:

[0030] Glass substrate, model GG5, purchased from Corning Glass;

[0031] Methyltrimethoxysilane, CAS No. 1185-55-3, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0032] 3-Aminopropyltriethoxysilane, CAS No. 919-30-2, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0033] γ-Glycidyloxypropyltrimethoxysilane, CAS No. 2530-83-8, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0034] Isopropyl alcohol, CAS No. 67-63-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0035] Silica sol, product number JR1007b, was purchased from Henan Jinrun New Materials Co., Ltd.;

[0036] Hexadecyltrimethylammonium bromide, CAS No. 57-09-0, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0037] Dodecyl dimethyl benzyl ammonium chloride, CAS No. 139-07-1, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0038] Didodecyl dimethyl ammonium chloride, CAS No. 3401-74-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0039] Propylene glycol butyl ether, CAS No. 29387-86-8, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0040] Epoxy silane oligomer, model LD-3168, purchased from Yangzhou Lida Resin Co., Ltd.;

[0041] Tetraethyl orthosilicate, CAS No. 78-10-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0042] (3-Mercaptopropyl)triethoxysilane, CAS No. 14814-09-6, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0043] Ethyl silicate 40, CAS No. 11099-06-2, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0044] 3-Aminopropyltriethoxysilane, CAS No. 919-30-2, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0045] Calcium sulfate whisker I, brand NP-M02-I30, diameter 5 μm, Jiangxi Fengzhu New Material Technology Co., Ltd.;

[0046] Calcium sulfate whisker II, brand NP-S04-YE, diameter 25 μm, Jiangxi Fengzhu New Material Technology Co., Ltd.;

[0047] Graphite I, model TS-4, particle size 3 μm, purchased from Qingdao Tianyuan Graphite Co., Ltd.;

[0048] Graphite II, product number G434785, particle size 30 μm, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0049] Graphite III, product number XT-0801-24-1, particle size 50 nm, purchased from Shanghai Xiangtian Nanomaterials Co., Ltd.;

[0050] N,N'-Dicyclohexylcarbodiimide, CAS No. 538-75-0, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0051] 4-Dimethylaminopyridine, CAS No. 1122-58-3, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0052] Acrylic acid, CAS No. 79-10-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0053] Example 1

[0054] This embodiment provides a preparation process for tempered corrosion-resistant colored coated glass, comprising the following steps:

[0055] Preparation of modified silica sol: In parts by weight, 60 parts of anhydrous ethanol and 20 parts of deionized water are mixed evenly, and then 50 parts of ethyl silicate 40 are added, stirred at 60°C for 2 hours, cooled to room temperature, 4 parts of hydrochloric acid are added and stirred for 24 hours, and then 6 parts of calcium sulfate whiskers I (with a diameter of 5 μm) are added and stirred for 30 minutes to obtain a silica sol coated with calcium sulfate; 3 parts of 3-aminopropyltriethoxysilane are added to 80 parts of the silica sol coated with calcium sulfate, the pH is adjusted to 7.6, and the reaction is stirred at 70°C for 12 hours to obtain the modified silica sol.

[0056] Preparation of graphite-doped epoxy silane oligomer: (1) 6 parts of graphite I (particle size 3 μm) were weighed and dispersed in a mixture of 20 parts of sulfuric acid and 30 parts of nitric acid for ultrasonic dispersion treatment, and then refluxed at 160°C for 1 hour. The product was washed with deionized water and dried to obtain acidified graphite; the 6 parts of the acidified graphite were dispersed in 120 parts of N,N-dimethylformamide to obtain a suspension, 8 parts of N,N'-dicyclohexylcarbodiimide, 3 parts of 4-dimethylaminopyridine and 10 parts of acrylic acid were added to the suspension, and reacted at 90°C for 20 hours under nitrogen atmosphere, filtered, washed and dried to obtain carboxylated graphite. (2) 40 parts of epoxy silane oligomer were heated to 60°C, and then 4 parts of carboxylated graphite were added and stirred for 40 minutes, and then vacuum degassed at 70°C for 30 minutes to obtain the graphite-doped epoxy silane oligomer.

[0057] Step S1: in parts by weight, 50 parts of tetraethyl orthosilicate, 60 parts of isopropanol, 3 parts of glacial acetic acid and 16 parts of deionized water are mixed evenly, hydrolyzed at room temperature for 40 hours, then heated to 80° C. for reaction for 2 hours, cooled to room temperature, added with 4 parts of (3-mercaptopropyl)triethoxysilane, stirred and reacted for 24 hours, to obtain a mercapto-silica prepolymer;

[0058] Step S2: in parts by weight, 35 parts of mercapto-silica prepolymer, 25 parts of silane coupling agent methyltrimethoxysilane, 18 parts of isopropanol, 30 parts of modified silica sol, 2 parts of surfactant hexadecyltrimethylammonium bromide and 8 parts of propylene glycol butyl ether are uniformly mixed, stirred at 50° C. for 2 h, and after cooling to room temperature, 10 parts of graphite-doped epoxy silane oligomer and 200 parts of isopropanol are added and stirred for 60 min to obtain a coating solution;

[0059] Step S3: coating the coating liquid on the surface of the glass substrate, and then performing a curing treatment (curing temperature of 160° C., curing time of 6 min) to obtain a tempered, corrosion-resistant colored coated glass.

[0060] Example 2

[0061] This embodiment provides a preparation process for tempered corrosion-resistant colored coated glass, comprising the following steps:

[0062] Preparation of modified silica sol: in parts by weight, 50 parts of anhydrous ethanol and 10 parts of deionized water are mixed evenly, then 40 parts of ethyl silicate 40 are added, stirred at 50°C for 2 hours, cooled to room temperature, 2 parts of hydrochloric acid are added and stirred for 20 hours, and then 4 parts of calcium sulfate whiskers I (with a diameter of 5 μm) are added and stirred for 20 minutes to obtain a silica sol coated with calcium sulfate; 1 part of 3-aminopropyltriethoxysilane is added to 60 parts of the silica sol coated with calcium sulfate, the pH is adjusted to 7.4, and the reaction is stirred at 60°C for 14 hours to obtain the modified silica sol.

[0063] Preparation of graphite-doped epoxy silane oligomer: (1) 4 parts of graphite I (particle size 3 μm) were weighed and dispersed in a mixture of 10 parts of sulfuric acid and 20 parts of nitric acid for ultrasonic dispersion treatment, and then refluxed at 150°C for 3 hours. The product was washed with deionized water and dried to obtain acidified graphite; the 4 parts of the acidified graphite were dispersed in 100 parts of N,N-dimethylformamide to obtain a suspension, 6 parts of N,N'-dicyclohexylcarbodiimide, 1 part of 4-dimethylaminopyridine and 8 parts of acrylic acid were added to the suspension, and reacted at 80°C for 24 hours under nitrogen atmosphere, filtered, washed and dried to obtain carboxylated graphite. (2) 30 parts of epoxy silane oligomer were heated to 50°C, and then 2 parts of carboxylated graphite were added and stirred for 60 minutes, and then vacuum degassed at 60°C for 40 minutes to obtain the graphite-doped epoxy silane oligomer.

[0064] Step S1: In parts by weight, 40 parts of tetraethyl orthosilicate, 50 parts of isopropanol, 1 part of glacial acetic acid and 12 parts of deionized water are mixed evenly, hydrolyzed at room temperature for 30 hours, then heated to 70° C. for reaction for 4 hours, cooled to room temperature, added with 2 parts of (3-mercaptopropyl) triethoxysilane, stirred and reacted for 20 hours, to obtain a mercapto-silica prepolymer;

[0065] Step S2: in parts by weight, 25 parts of mercapto-silica prepolymer, 15 parts of silane coupling agent 3-aminopropyltriethoxysilane, 16 parts of isopropanol, 20 parts of modified silica sol, 1 part of surfactant dodecyldimethylbenzyl ammonium chloride and 4 parts of propylene glycol butyl ether are uniformly mixed, stirred at 48° C. for 4 hours, and after cooling to room temperature, 6 parts of graphite-doped epoxy silane oligomer and 180 parts of isopropanol are added and stirred for 40 minutes to obtain a coating solution;

[0066] Step S3: coating the coating liquid on the surface of the glass substrate, and then performing a curing treatment (curing temperature is 80° C., curing time is 10 min) to obtain a tempered and corrosion-resistant colored coated glass.

[0067] Example 3

[0068] This embodiment provides a preparation process for tempered corrosion-resistant colored coated glass, comprising the following steps:

[0069] Preparation of modified silica sol: In parts by weight, 55 parts of anhydrous ethanol and 15 parts of deionized water are mixed evenly, then 45 parts of ethyl silicate 40 are added, stirred at 55°C for 3 hours, cooled to room temperature, 3 parts of hydrochloric acid are added and stirred for 22 hours, and then 5 parts of calcium sulfate whiskers I (with a diameter of 5 μm) are added and stirred for 25 minutes to obtain a silica sol coated with calcium sulfate; 2 parts of 3-aminopropyltriethoxysilane are added to 70 parts of the silica sol coated with calcium sulfate, the pH is adjusted to 7.5, and the reaction is stirred at 65°C for 13 hours to obtain the modified silica sol.

[0070] Preparation of graphite-doped epoxy silane oligomer: (1) 5 parts of graphite I (particle size 3 μm) were weighed and dispersed in a mixture of 15 parts of sulfuric acid and 25 parts of nitric acid for ultrasonic dispersion treatment, and then refluxed at 155°C for 2 hours. The product was washed with deionized water and dried to obtain acidified graphite; the 5 parts of the acidified graphite were dispersed in 110 parts of N,N-dimethylformamide to obtain a suspension, 7 parts of N,N'-dicyclohexylcarbodiimide, 2 parts of 4-dimethylaminopyridine and 9 parts of acrylic acid were added to the suspension, and reacted at 85°C for 22 hours under nitrogen atmosphere, filtered, washed and dried to obtain carboxylated graphite. (2) 35 parts of epoxy silane oligomer were heated to 55°C, and then 3 parts of carboxylated graphite were added and stirred for 50 minutes, and then vacuum degassed at 65°C for 35 minutes to obtain the graphite-doped epoxy silane oligomer.

[0071] Step S1: In parts by weight, 45 parts of tetraethyl orthosilicate, 55 parts of isopropanol, 2 parts of glacial acetic acid and 14 parts of deionized water are mixed evenly, hydrolyzed at room temperature for 35 hours, then heated to 75° C. for reaction for 3 hours, cooled to room temperature, added with 3 parts of (3-mercaptopropyl) triethoxysilane, stirred and reacted for 22 hours, to obtain a mercapto-silica prepolymer;

[0072] Step S2: in parts by weight, 30 parts of mercapto-silica prepolymer, 20 parts of silane coupling agent γ-glycidyloxypropyltrimethoxysilane, 17 parts of isopropanol, 25 parts of modified silica sol, 1.5 parts of surfactant didodecyldimethylammonium chloride and 6 parts of propylene glycol butyl ether are uniformly mixed, stirred at 49° C. for 3 hours, cooled to room temperature, added with 8 parts of graphite-doped epoxy silane oligomer and 190 parts of isopropanol and stirred for 50 minutes to obtain a coating solution;

[0073] Step S3: coating the coating liquid on the surface of the glass substrate, and then performing a curing treatment (curing temperature is 120°C, curing time is 8 minutes) to obtain a tempered and corrosion-resistant colored coated glass.

[0074] Comparative Example 1

[0075] The difference between this comparative example and Example 1 is that no (3-mercaptopropyl)triethoxysilane is added during the preparation of the silicon dioxide prepolymer.

[0076] Comparative Example 2

[0077] The difference between this comparative example and Example 1 is that commercially available silica sol is used instead of modified silica sol.

[0078] Comparative Example 3

[0079] The difference between this comparative example and Example 1 is that calcium sulfate whisker II is used instead of calcium sulfate whisker I to prepare the modified silica sol.

[0080] Comparative Example 4

[0081] The difference between this comparative example and Example 1 is that commercially available epoxy silane oligomer is used instead of graphite-doped epoxy silane oligomer.

[0082] Comparative Example 5

[0083] The difference between this comparative example and Example 1 is that graphite II is used instead of graphite I to prepare the graphite-doped epoxy silane polymer.

[0084] Comparative Example 6

[0085] The difference between this comparative example and Example 1 is that graphite III is used instead of graphite I to prepare the graphite-doped epoxy silane oligomer.

[0086] Performance Testing

[0087] The coated glasses prepared in the above examples and comparative examples were subjected to the following tests:

[0088] (1) Salt spray corrosion test: The test is carried out in accordance with the requirements of GB / T 10125-2021 Artificial atmosphere corrosion test salt spray test. The test result is the haze of the coated glass.

[0089] (2) Abrasion resistance test: The test is conducted in accordance with the requirements of GB / T 18915.2-2013 Coated glass Part 2: Low-emissivity coated glass. The test result is the visible light transmittance of the coated glass after abrasion.

[0090] (3) Hardness test: Test in accordance with the requirements of GB / T 6739-2022 Paints and varnishes - Determination of film hardness by pencil method.

[0091] Table 1 Performance test results

[0092]

[0093] From the above performance test results, it can be seen that the comprehensive performance of the tempered corrosion-resistant colored coated glass of Examples 1-3 is that the haze is 0.22~0.27%, the visible light transmittance after wear is 81.9~82.7%, and the hardness is 8H; this is mainly because the silica prepolymer in the coating solution is thiolated and modified silica sol and graphite-doped epoxy silane polymer are introduced, which effectively ensures that the coated glass has good corrosion resistance and effectively improves its wear resistance.

[0094] The comparative examples, however, were significantly inferior to the examples in the corresponding performance tests because they did not adopt the necessary technical solutions. Compared with Example 1, in the process of preparing the silica prepolymer in Comparative Example 1, no (3-mercaptopropyl)triethoxysilane was added, so the haze increased, the visible light transmittance decreased after wear, and the hardness decreased; compared with Example 1, in Comparative Example 2, commercially available silica sol was used to replace the modified silica sol, so the haze increased, the visible light transmittance decreased after wear, and the hardness decreased; compared with Example 1, in Comparative Example 3, calcium sulfate whisker II was used to replace calcium sulfate whisker I to prepare the modified silica sol, and because the diameter of calcium sulfate whisker II was too large, the modification effect was not good, so the haze increased, and the visible light transmittance decreased after wear. The transmittance decreased and the hardness decreased; compared with Example 1, Comparative Example 4 used commercially available epoxy silane oligomers to replace graphite-doped epoxy silane oligomers, and the haze increased, the visible light transmittance decreased after wear, and the hardness decreased; compared with Example 1, Comparative Example 5 used graphite II to replace graphite I to prepare graphite-doped epoxy silane oligomers. Since the particle size of graphite II was too large, the modification effect was not good, the haze increased, the visible light transmittance decreased after wear, and the hardness decreased; compared with Example 1, Comparative Example 6 used graphite III to replace graphite I to prepare graphite-doped epoxy silane oligomers. Since the particle size of graphite III was too small, the modification effect was not good, the haze increased, the visible light transmittance decreased after wear, and the hardness decreased. The above experimental results further prove the importance of the technical scheme defined in the present invention for its technical effect.

[0095] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A process for preparing tempered corrosion-resistant colored coated glass, characterized in that: include: In parts by weight, S1: 40-50 parts of tetraethyl orthosilicate, 50-60 parts of isopropanol, 1-3 parts of glacial acetic acid and 12-16 parts of deionized water are mixed evenly, hydrolyzed at room temperature for 30-40 hours, then heated to 70-80°C for reaction for 2-4 hours, cooled to room temperature, added with 2-4 parts of (3-mercaptopropyl) triethoxysilane, stirred and reacted for 20-24 hours, to obtain a mercapto-silica prepolymer; S2: 25-35 parts of mercapto-silica prepolymer, 15-25 parts of silane coupling agent, 16-18 parts of isopropanol, 20-30 parts of silica sol, 1-2 parts of surfactant and 4-8 parts of propylene glycol butyl ether are uniformly mixed, stirred at 48-50° C. for 2-4 hours, cooled to room temperature, added with 6-10 parts of epoxy silane oligomer and 180-200 parts of isopropanol and stirred for 40-60 minutes to obtain a coating solution; S3: coating the coating liquid on the surface of the glass substrate, and then performing a curing treatment to obtain a tempered and corrosion-resistant colored coated glass; The silica sol is a modified silica sol, and the preparation method is as follows: 50-60 parts of anhydrous ethanol and 10-20 parts of deionized water are uniformly mixed, and then 40-50 parts of ethyl silicate 40 are added, and stirred at 50-60°C for 2-4 hours, and after cooling to room temperature, 2-4 parts of hydrochloric acid are added and stirred for 20-24 hours, and then 4-6 parts of calcium sulfate whiskers are added and stirred for 20-30 minutes to obtain a silica sol coated with calcium sulfate; 1-3 parts of 3-aminopropyltriethoxysilane are added to 60-80 parts of the silica sol coated with calcium sulfate, the pH is adjusted to 7.4-7.6, and the reaction is stirred at 60-70°C for 12-14 hours to obtain the silica sol; The epoxy silane oligomer is a graphite-doped epoxy silane oligomer, and the preparation method is as follows: 30-40 parts of epoxy silane oligomer are heated to 50-60° C., then 2-4 parts of carboxylated graphite are added and stirred for 40-60 minutes, and then vacuum degassing is performed at 60-70° C. for 30-40 minutes to obtain the epoxy silane oligomer; The preparation method of the carboxylated graphite comprises: weighing 4 to 6 parts of graphite, dispersing the mixture in a mixed solution of 10 to 20 parts of sulfuric acid and 20 to 30 parts of nitric acid, and subjecting the mixture to ultrasonic dispersion treatment; then subjecting the mixture to a heat reflux reaction at 150 to 160° C. for 1 to 3 hours; washing the product with deionized water, and drying the product to obtain acidified graphite; dispersing 4 to 6 parts of the acidified graphite in 100 to 120 parts of N,N-dimethylformamide to obtain a suspension; adding 6 to 8 parts of N,N'-dicyclohexylcarbodiimide, 1 to 3 parts of 4-dimethylaminopyridine, and 8 to 10 parts of acrylic acid to the suspension; reacting the mixture at 80 to 90° C. for 20 to 24 hours under the protection of a nitrogen atmosphere; filtering, washing, and drying the mixture to obtain the obtained graphite; The particle size of the graphite is 2-5 μm.

2. The process for preparing the tempered corrosion-resistant colored coated glass according to claim 1, characterized in that: The diameter of the calcium sulfate whisker is 3-5 μm.

3. The process for preparing the tempered corrosion-resistant colored coated glass according to claim 1, characterized in that: The silane coupling agent is selected from any one of methyltrimethoxysilane, 3-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane or a combination of at least two thereof.

4. The process for preparing the tempered corrosion-resistant colored coated glass according to claim 1, characterized in that: The surfactant is selected from any one of cetyltrimethylammonium bromide, dodecyldimethylbenzylammonium chloride, didodecyldimethylammonium chloride or a combination of at least two thereof.

5. The process for preparing the tempered corrosion-resistant colored coated glass according to claim 1, characterized in that: The curing temperature of the curing treatment is 80-160° C., and the curing time is 6-10 minutes.

6. A temperable corrosion-resistant colored coated glass, characterized in that: Prepared according to the process according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Self-cleaning coated glass and preparation method thereof

    CN117142772B

  • Weather-proof double-layer high-antireflection coated glass and preparation method thereof

    CN111362589A

  • Gradient-refraction high-antireflection coated glass and preparation method thereof

    CN111439936A

  • High-durability super-hydrophilic coating with antibacterial and antifogging properties and preparation method of high-durability super-hydrophilic coating

    CN116135930A

  • Anti-reflection self-cleaning type coated photovoltaic glass and preparation method thereof

    CN118344021A